Improved cardiac troponin immunoassay for myocardial infarction diagnostics - Simonen, Sara (My University, 2025)
Human cardiac troponin is a trimeric protein complex consisting of subunits I, T, and C. An increase in cardiac troponin levels in the blood is characteristic for acute myocardial infarction. Unfortunately, various factors can cause interference in accurate troponin detection. Around 2-20 % of the population have cardiac troponin-specific autoantibodies (cTnAAbs) in the circulation. If cTnAAbs target the same troponin epitopes as the antibodies used in the assay, the measured signal in cardiac troponin test will be falsely low. In addition, elevated cardiac troponin levels are also detected in patients with non-myocardial infarction-related conditions and after strenuous exercise, thus potentially complicating clinical decision-making. The aim of this study was to develop a negative cTnAAb interference-free immunoassay that would be highly sensitive and specific for acute myocardial infarction. Different capture and tracer antibody combinations were tested, and upconverting nanoparticles were utilized for signal production. Patient samples with and without cTnAAbs were analyzed to test the performance of the new assay. The results from this study show that the new cardiac troponin immunoassay is less affected by negative cTnAAb interference than the previously developed immunoassay as the recoveries for troponin calibrator were significantly improved (mean 33% units) in cTnAAb-positive samples. In the future, more research is needed to conclude whether the new assay can distinguish acute myocardial infarction patients from other patient groups.
Keywords: acute myocardial infarction, cardiac troponin, cardiac troponin-specific autoantibodies, upconversion-linked immunosorbent assay, upconverting nanoparticles